KARAKTERISTIK IBU BERSALIN DENGAN SECTIO CAESAREA DI RUMAH SAKIT UMUM DAERAH DR. PIRNGADI MEDAN TAHUN 2011-2012 - Siti Maisyaroh Fitri Siregar; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Caesarean section is defined as the birth of the fetus through an incision in the abdominal wall and uterus wall. RI Department of Health in 2000 sets the number of births sectio Caesarea for referral teaching hospital or province 20% of all deliveries, while private hospitals 15% of all deliveries. To determine maternal characteristics by Caesarea section in Hospital of Dr. Pirngadi Medan research conducted in 2011-2012 with a descriptive case series design. Population of 858 women giving birth by Caesarean section and the sample was 87 mothers. Data were analyzed using ANOVA, t-test and chi-square. The highest proportion of women giving birth by caesarean section  in the age group 20-35 years old  78.20%, 70.11% Moslem, graduating high school / equivalent 83.91%, 75.86% housewives,, primiparous 34.48%, delivery within 2-3 years 55.17%, not 75.86% no history of the disease, no history of poor obstetric 75.68%, giving birth history by caesarean section 84.48%, 90.80% medical indications, maternal factors that previous history of caesarean Setion 42.19%, fetal distress fetal factors with 46.66%, not referenced / Dating own 42.53%, 96.55% normal birth weight, antenatal care at health centers / midwives 62.07%, long maintainability an average of 3.92 days, source their own expense the cost instead of 92.95%, while home mom living circumstances of 98.85%. There is no significant difference between the average treatment time is based on parity mothers (p = 0.808), history of disease (p = 0.354), poor obstetric history (p = 0.546). There is a significant difference between the average treatment time based on the circumstances when home mother (p = 0.019). There is no significant difference between the birth weight by Caesarean section indications (p = 0.746). Health professionals is expected to provide education on the benefits of normal parturition to pregnant  women especially during pregnancy,and pregnant women are expected to maintain nutrient intake and do regular antenatal care and routine physical and activities supported by the role of husband. Keyword : caesarean section, characteristic